Administrative Process Theory applied to Spectrum Regulation - Pinheiro, Guilherme Pereira (Law, State and Telecommunications Review, 2014)
Purpose ”“ This paper is intended to assess the efficacy of an administrative process theory as the foundation to regulate the radio spectrum in a scenario that contemplates private allocation of spectrum and the protection of public interest. Methodology/approach/design ”“ The text abides to the problem-action methodology, in which the paper is structured to respond to real problems arising from the flexibilization of the command-and-control model to regulate radio spectrum. Findings ”“ The administrative process theory is viable and necessary since it protects the public interest while it allows for the flexibility of the norms guiding the allocation and use of radio spectrum without delivering regulatory rents. Practical implications ”“ The paper works as a guideline to establish safe rules for altering rules and allocations of radio spectrum in Brazil. It also fills the void of a consistent study on the theme of spectrum reform, since it secures the public interest while allowing for spectrum property to be transferred to private parties.